A Review on Model Updating In Structural Dynamics - N. A. Z., Abdullah; M. S. M., Sani; M. M., Rahman; Izzuddin, Zaman (IOP Publishing, 2015)
This paper is a review of information and related studies concerning topic of model updating in structural dynamics. It is purposed to introduce and explain the important concept of the discussed subject in model updating area as well as to summarize the development and available guidance and method of conducting the study in this area. The review is structured by presenting an overview of general concept of finite element model updating in structural dynamics and the capabilities of finite element method as a tool in model updating. After the concept introduction, the reliable methodology to perform model updating, the limitation and the critical issues in model updating is discussed. The limitation and problems arise concerning correcting inaccurate finite element model is also discussed. This lead to issue of parameterization and regularization which the limitation and uncertainty in choosing the updating parameter is shown able to be overcome. Further studies on the elimination of systematic errors from both the measurements and the finite element model so that it can provide more reliable model updating is recommended.